Microbial assessment of indoor air of the applied microbiology laboratory, Nnamdi Azikiwe University, Awka, Nigeria - Ezemba AS; Nwabisi CM; Udemezue IO; Ezemba CC; Osuala OJ (Trends in Infection and Global Health, 2022)
Air is made up of enormous number of microorganisms mainly fungi and bacteria spores. Their estimation is important as an indication of cleanliness of any particular environment. The present study was carried out to assess microorganisms in indoor air of the Applied Microbiology laboratory of Nnamdi Azikiwe University, Awka. Prepared plates of Sabouraud Dextrose agar (SDA), Nutrient agar (NA), and Blood agar were exposed for ten minutes for culturing of microorganisms. The NA and Blood agar plates were incubated at 37oC for 24h while the SDA plate was incubated at room temperature for 48h. A total of ten (10) microorganisms were isolated from the samples. These include six (6) bacteria and four (fungal) species. The bacterial isolates include; Staphylococcus aureus, Bacillus sp., Pseudomonas aeruginosa, Escherichia coli, Streptococcus sp., and Proteus sp. The fungal isolates include Aspergillus sp., Penicillium sp., Fusarium sp., and Rhizopus sp. The most frequently isolated bacteria were Staphylococcus aureus and Bacillus sp. with 25% and 35% occurrence. Proteus sp., Streptococcus sp., E. coli, and P. aeruginosa had 20%, 10%, 5%, and 5% percentage occurrences respectively. Aspergillus and Penicillium sp. were the most frequently isolated fungal isolates with 40% and 30% occurrence respectively. Fusarium sp. and Rhizopus sp. both had 20% and 10% occurrence respectively. With this result, attention must be given to control those environmental factors which favor the growth and multiplication of microbes in the indoor air of the laboratory and air sterilization should be carried out to safeguard the health of users and workers.